Flow and heat transfer characteristics on a moving flat plate in a parallel stream with prescribed surface heat flux - Bachok @ Lati, Norfifah; Mohd Ishak, Anuar (WSEAS Press, 2010)
The boundary layer flow on a moving flat plate in a moving fluid with prescribed surface heat flux is studied. A finite difference scheme is used to solve the system of transformed governing equations. The features of the flow and heat transfer characteristics for different values of the governing parameters are analyzed and discussed. It is found that dual solutions exist when the plate and the free stream move in the opposite directions. The rate of heat transfer increases with increasing heat flux exponent parameter.